Anti-inflammatory activity of repurposed tyrosine kinase inhibitors in macrophages - Chaffey, L (2023)
Inflammation is a driver of human disease and an unmet clinical need exists for new anti-inflammatory medicines. As a key cell type involved in pathologies of both acute and chronic inflammatory disease, macrophages are an appealing therapeutic target for novel anti-inflammatory medicines. Drug repurposing, the use of existing medicines for novel indications, is an attractive and pragmatic strategy for the discovery of novel anti-inflammatory medicines due to reduced development costs and lower toxicity-associated failure risks than de novo drug discovery. In this thesis I set out to identify novel drug repurposing candidates with anti-inflammatory activity in macrophages. Using inhibition of NF-κB activity as a measure of anti-inflammatory activity, I performed a drug repurposing screen of 159 FDA-approved medicines in a macrophage reporter cell-line and identified sunitinib, a multiple tyrosine kinase inhibitor currently used as a treatment for advanced kidney cancers, to be an inhibitor of NF-κB activity. Further investigation of sunitinib in bone marrow derived macrophages revealed ability to inhibit production pro-inflammatory mediator production of TNFα, IL-6, IL-1β, CCL2, and NO. In vivo, I show that oral sunitinib treatment prior to LPS challenge reduces TNFα production and inflammatory gene expression, inhibits NF-κB nuclear translocation and reduces organ damage in a murine model of endotoxaemia. Additionally, as NF-κB mediated inflammatory signalling plays an important role in atherosclerosis progression, effects of sunitinib treatment were investigated in a model of hypercholesterolaemia. In Ldlr-/- mice fed a high fat diet, sunitinib treatment effectively reduced TNFα production and inflammatory gene expression but did not alter atherosclerotic plaque development or stability. The findings of this thesis support drug repurposing as a strategy for investigation of novel anti-inflammatory medicines and further exploration of sunitinib in inflammatory disease models will aid in determining its feasibility as a drug repurposing candidate for inflammatory disease.